Nezadovoljni odlašalci - Videčnik, Asja (Šolsko polje, 2011)
In this study we investigated procrastination in the academic context on students of the University of Ljubljana. According to recent studies, procrastination with tasks such as learning for an exam, writing a term paper and registering for exams has been linked to various personality traits, motivation, success rates etc. In this research we examined procrastination inrelationships with academic achievement and satisfaction (with life and withstudying). 181 students has reported some of their past grades, completedthe Procrastination Assessment Scale-Students PASS, (Solomon and Rothblum, 1984), Satisfaction with life scale SWLS (Diener et al., 1985) and aScale of academic satisfaction (Videčnik, 2009). Results are in broad agreement with previous studies. They show a mixed picture about the relationship between procrastination and grades, to some extent procrastination is weakly negatively correlated with some measures of school and academic success (eg, procrastination with learning for the exam is negatively associated with the average study grade), but elsewhere there are no significant correlations. Results also indicate that life satisfaction is weakly negatively correlated to procrastination on writing, studying, and the total PASS score. Academic satisfaction was moderately negatively associated to procrastination in all areas measured. Results of multiple regression analysis predicting study grades and academic satisfaction show that past grades and procrastination can explain 41.7% of the variance of the study average, and 52.3% of the variance of academic satisfaction. The findings give us insight in procrastination in school and academic context and help us to better understand academic satisfaction.
Keywords: procrastination; visokošolski študij; students; odlašanje; zadolžitve; grades; satisfaction with life; student; študenti; učni uspeh; academic satisfaction; zadovoljstvo